The Influence of Service Quality in the Issuance of SKCK on Public Satisfaction at Jatiyoso Police Section - Handoko, Frendy Prasetyo; Samsi, Samsi; Martomo, Yitno Puguh; Romadloni, Nova Tri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the influence of service quality on public satisfaction in the issuance process of Police Certificate of Good Conduct (SKCK) at Jatiyoso Police Sector. The background of this research is the urgency of public service quality as a performance indicator of government institutions, particularly in the police sector. This research employed a quantitative method with a descriptive correlational approach. Data was collected through questionnaires distributed to 146 SKCK applicants at Jatiyoso Police Section. Service quality was measured using five Servqual dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The analysis revealed that all dimensions positively affected public satisfaction, with Assurance and Empathy being the most dominant. Public satisfaction was categorized as high, as reflected in their willingness to reuse and recommend the service. The study recommends enhancing human resources, strengthening infrastructure, and implementing a continuous service evaluation system.